Pendekatan Dialogis Pada Pendidikan Islam dalam Surat Luqman Perspektif Tafsir Al-Maraghi - Enjang Burhanudin Yusuf; Helmi Salma Labibah; Siti Muzayinah; Dinda Ayu Riskiana Riskiana (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2026)
The negative impacts of the Industrial Revolution 4.0 include a crisis in human morality. This condition can lead to problems related to technology and knowledge, making it a significant challenge for educators. In fact, Islam has already provided guidance on how to educate children; however, rapid technological development has caused educators to pay less attention to children's education, particularly in aspects of aqidah (faith), akhlaq (morality), and muamalah (social conduct). The concept of child education recommended in Islam is found in the Qur'an, specifically in Surah Luqman verses 13–19, which describe how Luqman al-Hakim sets an example for his children in instilling moral values through a dialogical approach. This study aims to examine the moral messages of Luqman al-Hakim contained in Surah Luqman and to explore Islamic education from a moral perspective. The results of the study show that there are four moral messages in Surah Luqman in accordance with Islamic education: instilling aqidah in children, teaching gratitude, encouraging devotion to Allah and respect for parents, habituating righteous deeds, and teaching noble character and proper ethics in social interactions.